Financial statement and budget report 1985-86: copy of financial statement and budget report 1985-86 as laid before the House by the Chancellor of the exchequer when open in budget - Great Britain; Great Britain (London : H.M.S.O., 1998)
Copy of Financial Statement and Budget Report 1985-86 as laid before the House by the Chancellor of the Exchequer when opening the budget. The report covers: The Budget proposals; Medium-term financial strategy; The Economy: recent developments and prospects to mid-1986; The budget tax and national proposals in details; Public expenditure and Public sector transactions.
"Copy of financial statement and budget report ... as laid before the House of Commons by the Chancellor of the Exchequer when opening the budget."
Some issues have also a distinctive title.
rpm 20/02/2019
Ref
Keywords: Finance, Public; Economic policy; Finance, Public; Great Britain; Great Britain